2013
DOI: 10.3928/02793695-20130327-01
|View full text |Cite
|
Sign up to set email alerts
|

Prevention Strategies to Reduce Falls in Psychiatric Settings

Abstract: A Fall Committee was developed in response to an increase in the rate of falls by patients at a primarily behavioral health, urban teaching hospital in the mid-Atlantic region of the United States. The Fall Committee identified interventions to potentially lessen the number of patient falls and areas where documentation could be improved to better describe an incident in the medical record. The Fall Committee developed paperwork to be completed after each patient fall and made changes to the low fall risk and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…The studies within the risk management theme (Table 1) predominantly concentrated on how to efficiently calculate the risk of, or enhance conditions for assessments of, suicide, self-harm, violence, or falls 14,17,20–22,26,28,29,32,34–36 . These studies highlighted the importance of carefully choosing the right instrument to measure risk and showed that a poorly conducted risk assessment process can impact practice, policies, and management strategies in an undesirable way 22,24,25,27 . It is even argued that interventions to reduce risk, in some cases, can give rise to and legitimize ineffective and unethical practices within psychiatric inpatient care 30 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies within the risk management theme (Table 1) predominantly concentrated on how to efficiently calculate the risk of, or enhance conditions for assessments of, suicide, self-harm, violence, or falls 14,17,20–22,26,28,29,32,34–36 . These studies highlighted the importance of carefully choosing the right instrument to measure risk and showed that a poorly conducted risk assessment process can impact practice, policies, and management strategies in an undesirable way 22,24,25,27 . It is even argued that interventions to reduce risk, in some cases, can give rise to and legitimize ineffective and unethical practices within psychiatric inpatient care 30 .…”
Section: Resultsmentioning
confidence: 99%
“…14,17,[20][21][22]26,28,29,32,[34][35][36] These studies highlighted the importance of carefully choosing the right instrument to measure risk and showed that a poorly conducted risk assessment process can impact practice, policies, and management strategies in an undesirable way. 22,24,25,27 It is even argued that interventions to reduce risk, in some cases, can give rise to and legitimize ineffective and unethical practices within psychiatric inpatient care. 30 Other studies noted that adequate assessment of a patient's risk of adverse events or suicide required enhancing the ability of the staff to engage in an empathic dialogue with the patient.…”
Section: Risk Managementmentioning
confidence: 99%
“…Falls are one of the most critical patient safety concerns in all hospital settings (Ulrich et al, 2008), and this includes psychiatric hospitals. The physical environment has been recognized as a contributing factor to patient falls constituting 9% to 16% of falls (Al-Khatib et al, 2013). This study reviewed patterns of patient falls in relation to the physical environment within the context of a psychiatric hospital from a 7-year period of sentinel event reports and contributes new insights regarding environmental design factors related to inpatient falls in a psychiatric hospital.…”
Section: Discussionmentioning
confidence: 99%
“…A fim de evitar danos graves e até mesmo a morte decorrente da queda, é necessária uma ferramenta de avaliação de risco eficiente e confiável, que identifique precocemente os riscos e auxilie o planejamento e a implementação de intervenções para prevenção de quedas (16)(17) . (18)(19) . Além disso, um eficiente instrumento de avaliação de risco de queda pode ser aplicado por equipes multidisciplinares para identificar fatores de risco e o desenvolvimento de planos de intervenção (20) .…”
Section: Introductionunclassified